Is There a Bidirectional Relationship Between Maternal Well-Being and Child Behavior Problems in Autism Spectrum Disorders? Longitudinal Analysis of a Population-Defined Sample of Young Children - Damon Berridge (Autism Research, 2013)
Behavior problems and maternal well-being in ASD